Environmental Pollutants and Contaminants of Emerging Concern: An African Perspective - Chinaza Awuchi; Ikechukwu Amagwula (Newinera Publisher, 2021)
This review focuses on the environmental pollutants and contaminants of emerging concern in Africa. There is increasing reports and identification of ecotoxicological impact of contaminants of emerging concern (CECs), such as plastic, pharmaceutical products, modern pesticides, and personal care products, in terrestrial and aquatic environment within Africa. Identification of CECs, including pharmaceuticals, plastic wastes, pesticide residues, fungal toxins, and personal care products, have been documented in African region including in sediments, sludge, treated drinking water, surface water, wastewater, groundwater, land, solid deposits, etc. Some of the emerging pollutants of concern to environment and humans include lindane, heptachlor, endrin, endosulfan, dieldrin, dichlorodiphenyltrichloroethane (DDT), benzaldehyde, aldrin, bisphenol A, phthalates, bisphenol S, etc. There is need for more studies to identify and quantify the existing and more emerging pollutants.